2007
DOI: 10.1016/j.tox.2007.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation and gene expression in livers of newborn mice transplacentally exposed to a hepatocarcinogenic dose of inorganic arsenic

Abstract: Our prior work showed that brief exposure of pregnant C3H mice to inorganic arsenic-induced hepatocellular carcinoma (HCC) formation in adult male offspring. The current study examined the early hepatic events associated with this oncogenic transformation. Pregnant mice were exposed to a known carcinogenic dose of arsenic (85 ppm) in the drinking water from gestation days 8 to 18. The dams were allowed to give birth and liver samples from newborn males were analyzed for arsenic content, global DNA methylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 37 publications
5
101
0
Order By: Relevance
“…We found that those who started drinking well water from birth, still drank at enrollment, and drank it for long period were at a significantly increased risk of urinary cancer, especially urothelial carcinoma. Evidence from experimental studies (19)(20)(21)(22) showed that early-life exposure to arsenic may increase the health risks during early childhood and later in life. Up to date, only one ecologic study (23) conducted in Chile showed that exposure to arsenic in drinking water during early childhood or in utero was associated with an increased mortality in young adults from both malignant and nonmalignant lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We found that those who started drinking well water from birth, still drank at enrollment, and drank it for long period were at a significantly increased risk of urinary cancer, especially urothelial carcinoma. Evidence from experimental studies (19)(20)(21)(22) showed that early-life exposure to arsenic may increase the health risks during early childhood and later in life. Up to date, only one ecologic study (23) conducted in Chile showed that exposure to arsenic in drinking water during early childhood or in utero was associated with an increased mortality in young adults from both malignant and nonmalignant lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis that was unadjusted for cellular composition, one CpG loci (cg26587014) located in chromosome 19 and not annotated to any gene was differentially methylated in arterial tissue in relation to arsenic exposure using a Bonferroni threshold for statistical significance (P < 1.33 £ 10 ¡7 ). Controlling for the false discovery rate at 5% (q-value < 0.05) revealed 2,105 CpGs that were differentially methylated relative to log 2 -transformed maternal drinking water arsenic.…”
Section: Locus-by-locus Analysismentioning
confidence: 99%
“…17,18 Therefore, it is postulated that epigenomic regulation including, but not limited to, DNA methylation is a potential mechanism of arsenic induced carcinogenesis and latent disease risk. 2,19,20 Other likely interacting mechanisms of early life exposure to arsenic and latent disease risk include the development of cancer stem cells and perturbations of immune function. 2 Several human studies have evaluated the impact of prenatal arsenic exposure on the cord blood and whole blood epigenome.…”
Section: Introductionmentioning
confidence: 99%
“…9 While it is not fully understood how early life exposure to arsenic would lead to increased susceptibility to disease later in life, experimental studies have shown that in utero exposure to arsenic alters DNA methylation in offspring. [10][11][12][13][14] There is also evidence from epidemiological studies that arsenic exposure from drinking water alters DNA methylation in whole blood collected in adults. [15][16][17] Recently, our group showed that maternal exposure Prenatal arsenic exposure is associated with increased risk of disease in adulthood.…”
Section: Introductionmentioning
confidence: 99%